Iraq Crude Oil Exports, (January, February, March, April, May, June)/ 2022 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2024)
List of Tables Table 1. Iraq Crude Oil Exports – January 2022 Table 2. Iraq Crude Oil Exports – February 2022 Table 3. Iraq Crude Oil Exports – March 2022 Table 4. Iraq Crude Oil Exports – April 2022 Table 5. Iraq Crude Oil Exports – May 2022 Table 6. Iraq Crude Oil Exports – June 202